Construction of GQDs‐Decorated Ultrathin Bi2WO6 Nanosheets Hydrogel: a Recyclable‐Flexible Platform with Excellent Piezo‐Photocatalytic Activity for High‐Performance Water Decontamination and its Theoretical Interpretation. (1st November 2021) - Wei, Ziye; Gao, Hongzhi; Fu, Guoshuai; Yang, Guowei; Li, Jiling; Liu, Pu
Abstract: It is demonstrated that, by using the electronic reconstruction of ultrathin Bi2 WO6 (BWO) nanosheets with graphene quantum dots (GQDs) upon a unique process of laser irradiation in liquid (LAL), a kind of GQDs modified BWO nanosheets under metastable state were synthesized, which performed excellent visible‐light piezo‐photocatalytic organics degradation. Furthermore, using commercial cpolyacrylamids (PAM) as the additional materials, a kind of electronic reconstruction GQDs‐BWO nanosheets hydrogel was achieved by dispersed the functionalized powders into a super absorbent polymers (SAPs) system upon in situ polymerization method, which showed that it is a bracing idea to use SAPs for water decontamination reactors to enable full use of vibration energy synergistic with light of nature to driven pollution degradation. First‐principles calculation was also simultanously performed in this study. This study may provide a new enlightenment on fabricating novel 2D nanomaterials hydrogel for efficient effluent purification and potentially other environmental or energy applications. Abstract : Schematic illustration of the mechanism by graphene quantum dots‐Bi2WO6‐polyacrylamide (GQDs‐BWO‐PAM) hydrogel under simultaneous visible light and ultrasonic vibration.